Central recirculation zones and instability waves in internal swirling flows with an annular entry - Wang, Yanxing; Yang, Vigor (Physics of fluids (1994), 2018)
The characteristics of the central recirculation zone and the induced instability waves of a swirling flow in a cylindrical chamber with a slip head end have been numerically investigated using the Galerkin finite element method. The effects of Reynolds number as well as swirl level adjusted by the injection angle were examined systematically. The results indicate that at a high swirl level the flow is characterized by an axisymmetric central recirculation zone (CRZ). The fluid in the CRZ takes on a solid-body rotation driven by the outer main flow through a free shear layer. Both the solid-body rotating central flow and the free shear layer provide the potential for the development of instability waves. When the injection angle increases beyond a critical value, the basic axisymmetric flow loses stability, and instability waves develop. In the range of Reynolds numbers considered in this study, three kinds of instability were identified: inertial waves in the central flow, and azimuthal and longitudinal Kelvin-Helmholtz waves in the free shear layer. These three types of waves interact with each other and mix together. The mode selection of the azimuthal waves depends strongly on the injection angle, through the perimeter of the free shear layer. Compared with the injection angle, the Reynolds number plays a minor role in mode selection. The flow topologies and characteristics of different flow states are analyzed in detail, and the dependence of flow states on the injection angle and Reynolds number is summarized. Finally, a linear analysis of azimuthal instabilities is carried out; it confirms the mode selection mechanisms demonstrated by the numerical simulation.